Solution NMR Backbone Assignment of the C-Terminal Region of Human Dynein Light Intermediate Chain 2 (LIC2-C) Unveils Structural Resemblance with Its Homologue LIC1-C - Henen, Morkos A.; Paukovich, Natasia; Prekeris, Rytis; Vögeli, Beat (Magnetochemistry, 2023)
Dynein, a homodimeric protein complex, plays a pivotal role in retrograde transportation along microtubules within cells. It consists of various subunits, among which the light intermediate chain (LIC) performs diverse functions, including cargo adaptor binding. In contrast to the vertebrate LIC homolog LIC1, LIC2 has received relatively limited characterization thus far, despite partially orthogonal functional roles. In this study, we present a near-to-complete backbone NMR chemical shift assignment of the C-terminal region of the light intermediate chain 2 of human dynein 1 (LIC2-C). We perform a comparative analysis of the secondary structure propensity of LIC2-C with the one previously reported for LIC1-C and show that the two transient helices in LIC1 that interact with motor adaptors are also present in LIC2.